Три новых вида Acaronemus (Acariformes, Tarsonemidae) из Крыма - Шаронов, А.А. (Вестник зоологии, 1984)
Three New Species of the Genus Acaronemus (Acariformes, Tarsonemidae) from the
Crimea. Sharonov A. A.— Vestn. zool., 1984, No. 3. The species from the Crimea, described
as new, are assigned to originally monotypic genus Acaronemus Lindquist et Smiley, 1978 (type species by original designation: Tarsonemus destructor Smiley et
Landwehr, 1976): A. modestus sp. n., A. multus sp. n. and A. tauricus sp. n. A key
to all four hitherto known species.